2013
DOI: 10.4236/ojmm.2013.31013
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Leukemia Virus Gene Segment Detected in Human Breast Tissue

Abstract: Background: Bovine Leukemia Virus (BLV) is known by infections in bovine cattle and produce, in 30% of infected animals, persistent lymphocytosis significantly impacts the beef industry. It has been proposed that this virus could be transmitted to humans and be present in cases of breast cancer. Aim: to determine the presence of 380 bp of gag gene segment of BLV in paraffin-embedded breast tissue. Study Design: Control-case study. Methodology: 106 tissue samples were collected. 53 were cancer positive samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…The current study results showed that BLV could be detected by in situ PCR in 22.36% of the females that the malignant breast tissue specimens originated in them. In similar studies performed in other countries, BLV DNA was present in a higher percentage of malignant tested tissues [6,13,33]. This difference could be due to the fact that samples were not processed from the beginning by the same operator, or, instead, since the number of samples was not large enough.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The current study results showed that BLV could be detected by in situ PCR in 22.36% of the females that the malignant breast tissue specimens originated in them. In similar studies performed in other countries, BLV DNA was present in a higher percentage of malignant tested tissues [6,13,33]. This difference could be due to the fact that samples were not processed from the beginning by the same operator, or, instead, since the number of samples was not large enough.…”
Section: Discussionmentioning
confidence: 85%
“…Other areas of the BLV genome transcribing microRNAs and other RNAs that regulate microRNAs, are recently associated with maintaining the transformed state of BLV-infected cells [29,30]. Retrotranscribed BLV DNA is detected in human breast tissue by standard solution PCR [13] and in situ PCR [6]. BLV structural proteins gp51 and p24 are also detected in human breast tissue [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ряд публикаций указывают на обнаружение провирусной ДНК вируса бычьего лейкоза в эпителиальных клетках молочных желез женщин, в том числе больным раком молочной железы, с выдвижением концепции, что вирус бычьего лейкоза влияет на дестабилизацию генома хозяина и приводит к развитию ракового перерождения клетки [15][16][17][18][19].…”
unclassified
“…Environmental factors such as exposure to ionizing radiation, inheriting certain genes such as BRCA1 and BRCA2, and, most importantly, lifestyle have been associated with an increase in the risk of breast cancer. For instance, the link between breast carcinogenesis and naturally occurring substances such as heterocyclic amines (HCAs), insulin-like growth hormone (IGF-I), animal estrogen (E2), and bovine leukaemia virus (BLV), which are ubiquitous in western and modern diets, have been substantiated with a vast body of evidence [4][5][6][7][8][9][10][11]. Nonetheless, not much has been done in updating the dietary guidelines and food policies to address the role of these substances, and similar ones, in cancer epidemic.…”
Section: Introductionmentioning
confidence: 99%